the IMPLEMENTASI PENGGUNAAN ANTRIAN ONLINE MELALUI APLIKASI MOBILE JKN TINJAUAN LITERATUR: IMPLEMENTASI PENGGUNAAN ANTRIAN ONLINE MELALUI APLIKASI MOBILE JKN TINJAUAN LITERATUR - Taufik, Anvika; Alhamda, Syukra; Gustina Irawan , Yeyen (STIKES Garuda Putih, 2025)
Background:Mobile JKN is a digital innovation by BPJS Kesehatan aimed at improving access and efficiency in healthcare services. One of its key features is the online queuing system, which is designed to reduce patients’ waiting time. Objective:This study aims to analyze the relationship between the use of the Mobile JKN application and patient waiting times or queues in healthcare facilities across Indonesia, based on a review of relevant studies. Methods:This research was conducted using a literature review method by analyzing and examining scientific journal articles sourced from Google Scholar, published between January 1, 2018 and March 31, 2025. The article search was performed using the keywords “Mobile JKN,” “waiting time,” and “online registration.” The objective was to identify the factors that influence the use of the online registration system within the Mobile JKN application. Results:Most studies indicate that the use of Mobile JKN can significantly reduce patient waiting times, especially when accompanied by assistance or intensive monitoring. However, several studies also reveal that low digital literacy, limited infrastructure, and lack of user education remain key barriers to the effective implementation of the application. Conclusion:eight articles were found after applying the inclusion and exclusion criteria. Mobile JKN has great potential to improve service efficiency through its online queuing feature. However, its success largely depends on the readiness of infrastructure, public education, and sustained support from healthcare facilities. An integrative effort involving technology, human resources, and service policies is essential to ensure the successful nationwide adoption of this system.